Microglial aging in the healthy CNS: phenotypes, drivers, and rejuvenation - Wong, Wai T. (Frontiers in Cellular Neuroscience, 2013)
Neurodegenerative diseases such as Alzheimer’s disease, Parkinson’s disease, and age-related macular degeneration, share two characteristics in common: 1) a disease prevalence that increases markedly with advancing age, and 2) neuroinflammatory changes in which microglia, the primary resident immune cell of the CNS, feature prominently. These characteristics have led to the hypothesis that pathogenic mechanisms underlying age-related neurodegenerative disease involve aging changes in microglia. If correct, targeting features of microglial senescence may constitute a feasible therapeutic strategy. This review explores this hypothesis and its implications by considering the current knowledge on how microglia undergo change during aging and how the emergence of these aging phenotypes relate to significant alterations in microglial function. Evidence and theories on cellular mechanisms implicated in driving senescence in microglia are reviewed, as are “rejuvenative” measures and strategies that aim to reverse or ameliorate the aging microglial phenotype. Understanding and controlling microglial aging may represent an opportunity for elucidating disease mechanisms and for formulating novel therapies.